2004
DOI: 10.1542/peds.113.1.e57
|View full text |Cite
|
Sign up to set email alerts
|

Deep Venous Thrombosis in Children With Diabetic Ketoacidosis and Femoral Central Venous Catheters

Abstract: ABSTRACT. Objective. To describe findings of deep venous thrombosis (DVT) in association with femoral central venous catheter (CVC) placement for intensive fluid management in children with diabetic ketoacidosis (DKA) secondary to type 1 diabetes.Design. Retrospective cohort study. Setting. Pediatric intensive care unit (PICU) of a children's referral medical center.Patients. DKA patients from 1998 to 2002 of children with DKA with and without CVC placement. DKA patients were also compared with all PICU patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
52
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 19 publications
(43 reference statements)
1
52
1
Order By: Relevance
“…The corrected sodium level was 144 mmol/L with a calculated serum osmolarity of 331 mOsm/L. We agree that patients with DKA have hyperosmolarity because of hyperglycemia and hypernatremic dehydration, and we 1 and others 2,3 have suggested that the hyperosmolarity contributes to the prothrombotic tendency of children with DKA.…”
Section: Dka and Thrombosissupporting
confidence: 63%
See 1 more Smart Citation
“…The corrected sodium level was 144 mmol/L with a calculated serum osmolarity of 331 mOsm/L. We agree that patients with DKA have hyperosmolarity because of hyperglycemia and hypernatremic dehydration, and we 1 and others 2,3 have suggested that the hyperosmolarity contributes to the prothrombotic tendency of children with DKA.…”
Section: Dka and Thrombosissupporting
confidence: 63%
“…2 The mostly adult entity of hyperosmolar nonketotic coma has had various degrees of association with thrombosis, 2,3 as has extreme hypernatremia in breast-feeding neonates. 4 Recent evidence has also demonstrated that among children with DKA, there is a higher incidence of deep venous thrombosis with femoral central venous lines.…”
Section: Dka and Thrombosismentioning
confidence: 99%
“…4 Recent evidence has also demonstrated that among children with DKA, there is a higher incidence of deep venous thrombosis with femoral central venous lines. 5,6 Serum glucose and sodium concentrations and hence effective plasma osmolarity were significantly higher in those patients with blood clots. 5 Although there is no direct evidence for its efficacy, our practice has been to use prophylactic anticoagulation in patients with DKA who are in a significant hyperosmolar state, as well as to eliminate the use of femoral catheters in patients with these risk factors.…”
Section: Dka and Thrombosismentioning
confidence: 96%
“…5,6 Serum glucose and sodium concentrations and hence effective plasma osmolarity were significantly higher in those patients with blood clots. 5 Although there is no direct evidence for its efficacy, our practice has been to use prophylactic anticoagulation in patients with DKA who are in a significant hyperosmolar state, as well as to eliminate the use of femoral catheters in patients with these risk factors. There is significant controversy surrounding the dose of anticoagulant therapy, specifically whether the efficacy of dosages for prophylaxis of deep venous thrombosis outweighs the risks associated with full systemic anticoagulation.…”
Section: Dka and Thrombosismentioning
confidence: 96%
“…In the medical literature there have been few reported cases CVC related VTE in DKA children without known risk factors. [208][209][210]. Thus, DKA and its treatment may promote a prothrombotic state and activation of vascular endothelium, predisposing to thrombosis.…”
Section: Peripheral Venous Thrombosismentioning
confidence: 99%